GAMBARAN PENGETAHUAN IBU HAMIL TENTANG KURANG ENERGI KRONIS (KEK) DI PUSKESMAS SUNGAI BILU BANJARMASIN - Ari Lestari, Nur Cahyani; Dwi Aningsih, Baharika Suci; Utami, Syahrida Wahyu (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
Based on the registration data of the Banjarmasin City Health Office in 2019-2020 the incidence of Chronic Energy Deficiency (KEK) in pregnant women at Sungai Bilu Health Center Banjarmasin in 2019-2020 has increased, namely in 2019 as many as 13 people (6.5%) and 45 people (22.1%) in 2020. The purpose of the study: to describe the knowledge of pregnant women about SEZ at the Sungai Bilu Health Center, Banjarmasin in 2021. The type of research used was descriptive method (described) with a population of 206 people and a sample of 68 people. The results of the study of 68 pregnant women who came to Sungai Bilu Health Center Banjarmasin some of them had less knowledge, namely 32 (47.0%) respondents, and 23 (33.8%) respondents who had good knowledge 13 (19.2%) respondents. Conclusion: The results of this study can be concluded that the knowledge of pregnant women in recognizing SEZs at the Sungai Bilu Health Center Banjarmasin in 2021 is partially knowledgeable, as many as 32 (47.0%) respondents